A compact and wideband vertically polarized monopole antenna - Omar, Ahmed Abdelmottaleb (2021)
The design of a compact, wideband antenna with omnidirectional radiation pattern is proposed. The antenna occupies a cylindrical volume and is composed of a conducting body of revolution, parasitic top ring shorted to the ground plane via a meander line, dielectric material, and two parasitic metallic posts. The conducting body of revolution is employed to act as a wideband feeding structure. The parasitic top ring with the meander line and the dielectric material is utilized to reduce the lowest frequency of operation; hence, size reduction is achieved. The detailed analysis of the antenna performance is provided with the help of vector surface current distribution. The proposed design provides a VSWR lower than 2.5:1 from 0.69 to 3.35 GHz with a bandwidth of 4.86:1. The antenna has a diameter of 0.115λmax and a height of 0.092λmax, where λmax is the free-space wavelength at the lowest frequency of operation. An antenna prototype is designed, fabricated, and measured. The measured VSWR is consistent with the simulated one. The measured maximum realized gain varies from 1.3 to 6 dBi. The total efficiency of the proposed antenna is above 80% within the operating band. By excluding the impedance mismatching, the simulated radiation efficiency is found to be above 93%. A good agreement is achieved between simulated and measured far-field radiation patterns.